The Indian Textile Industry: International Competitiveness - gunja, saluja (2008)
This paper identifies the international competitiveness of Indian textile industry. The Indian textile industry is one of the largest in the world, with a huge raw material and textile manufacturing base. Due to its extensive input, it occupies an exceptional place in the Indian market place. Today this sector is highly globalised but, it is further organizing itself to crave a bigger share to become the market leader. This large and ancient industry has carved out a special niche for itself as a facilitator of the county's economic growth and participative development. However, since few years this industry was striving to recover from a stage of stagnation but today it is growing at a very fast pace. This dissertation elucidates the relevant literature on international competitiveness, and further describes various macro economic factors which are affecting the economy of India. The researcher has used qualitative research methods in order to satisfy the objectives of this research. Later, the findings have been discussed with the industry's SWOT analysis. Lastly, the conclusion of this study discusses the limitations and recommendations.